A conservative approach in management of a molar incisor hypomineralization: Report of a case - Ramneet Kaur; Akhil Sharma; Vasundhara Pathania; Ruchika Kundra (Wolters Kluwer Medknow Publications, 2020)
Enamel hypomineralization is a developmental defect of enamel occurs due to disturbances in early calcification or maturation during amelogenesis. It can be seen in both the primary and permanent dentitions. These defects usually involves permanent molars and incisors presenting as well demarcated, asymmetrical opaque lesions varying from white to yellow or brown in color. Partial or complete loss of enamel in these soft, porous, and hypomineralized teeth leads to hypersensitivity, impaired masticatory functions, and esthetics. Difficulty in achieving local anesthesia and managing behavior of a young and fearful child makes it even more challenging to the clinicians that necessitate the use of a more conservative approach during the dental treatment. Therefore, we are presenting here a case of diagnosis, restorative, and esthetic correction of molar incisor hypomineralization in a 12-year-old child with least invasive clinical procedures.